(untitled) (PROKLA. Journal of Critical Social Science, 2019)
German social democracy is in crisis, is abolishing itself – and there are no more possibilities for rescue. The Social Democratic Party of Germany (SPD) has had its time, this time has now expired: it has always shown itself to be a state bearer to the bitter end, has established itself in the “Model Germany” and has completely failed in the face of all the more recent urgent challenges such as those of the immigration society and the climate crisis. Social democracy no longer has a historical project.